1984
DOI: 10.1177/019459988409200319
|View full text |Cite
|
Sign up to set email alerts
|

Histology of Extruded Plasti‐Pore Ossicular Prostheses

Abstract: Twenty-three Plasti-Pore ossicular prostheses removed from the human middle ear following partial or total extrusion were investigated by light microscopy. No specific tissue reaction other than the ingrowth of histiocytic cells elicited from the porous Plasti-Pore was found. The only histologic feature typical of extruded prostheses was the presence of granulocytes in all parts extruded. In our opinion this finding was the inflammatory reaction following the ischemic necrosis of tissue grown inside the pores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
1
2
0
3
Order By: Relevance
“…However, light-and electron-microscopic in vivo animal studies identified foreign body reactions adjacent to the implant and phagocytic consumption of the material [48]. Explanted prostheses showed microscopic desintegration after years of implantation and microrganisms were regularly found in the pores of extruded prostheses [49][50][51][52]. The experimental reservations of many authors about this materials are in accordance with long term clinical observations reporting extrusion rates as high as 60 % and poor long term hearing results [51,53].…”
Section: Polyethylenesupporting
confidence: 60%
“…However, light-and electron-microscopic in vivo animal studies identified foreign body reactions adjacent to the implant and phagocytic consumption of the material [48]. Explanted prostheses showed microscopic desintegration after years of implantation and microrganisms were regularly found in the pores of extruded prostheses [49][50][51][52]. The experimental reservations of many authors about this materials are in accordance with long term clinical observations reporting extrusion rates as high as 60 % and poor long term hearing results [51,53].…”
Section: Polyethylenesupporting
confidence: 60%
“…Zumindest sind bei explantierten Kunststoffprothesen regelmäßig Bakterien nachzuweisen gewesen [6]. Zumindest sind bei explantierten Kunststoffprothesen regelmäßig Bakterien nachzuweisen gewesen [6].…”
Section: Für Die Manifestation Einer Infektion Sind Zahl Und Aggressiunclassified
“…Kleinere Partikel wurden phagozytiert, wobei diese Beobachtungen für Polycel-, Plastipore-und Proplastprothesen galten [103]. In den Poren abgestoßener Prothesen fanden sich regelmäßig bakterielle Mikroorganismen [5,34,91,92].…”
Section: Klinische Anwendungunclassified
“…Der Endplatte aufgelegte Knorpelscheiben reduzierten die Abstoßungsrate auf 10-15% [21,34,78]. Der Endplatte aufgelegte Knorpelscheiben reduzierten die Abstoßungsrate auf 10-15% [21,34,78].…”
Section: Klinische Anwendungunclassified